Relationship between self-care compliance, trust, and satisfaction among hypertensive patients in China - Zhou, Chi; Chen, Jingchun; Tan, Fang; Lai, Sihong; Li, Xu; Pu, Ke; Wu, Jiahui; Dong, Yin; Zhao, Falin (Frontiers in Public Health, 2023)
Hypertension is a growing public health concern worldwide. It is a leading risk factor for all-cause mortality and may lead to complications such as cardiovascular disease, stroke, and kidney failure. Poor compliance of hypertension patients is one of the major barriers to controlling high blood pressure. Compliance is not ideal among Chinese patients, and increasing patient self-care compliance with hypertension is necessary. This article analyzes the status of self-care compliance, trust, and satisfaction among Chinese hypertensive patients using cross-sectional data from Zhejiang Province. We use a multi-group structural equation model (MGSEM) to compare the interrelationships across genders. The study’s findings show that the average trust, satisfaction, and compliance scores are 3.92 ± 0.55, 3.98 ± 0.61, and 3.33 ± 0.41, respectively. Female patients exhibit higher average total scores for trust and compliance than male patients. The SEM results indicate that trust has a direct positive association with compliance ( = 0.242, 95% CI: [0.068, 0.402]) and satisfaction ( = 0.260, 95% CI: [0.145, 0.367]), while their satisfaction is not directly associated with compliance. The results of MGSEM show that trust has an indirect effect on compliance in the male group through satisfaction (= 0.051, P < 0.05, 95% CI: [0.012, 0.116]). In the female group, trust has a direct effect on satisfaction (= 0.235, P < 0.05, 95%CI: [0.041, 0.406]) and compliance (= 0.319, P < 0.01, 95% CI: [0.086, 0.574]). This study reveals the mechanisms of self-care compliance, trust, and satisfaction among Chinese hypertensive patients. Its findings may serve as a reference for guiding primary healthcare providers to improve hypertension patients’ compliance and implement gender-targeted health interventions.